Utility of SpeedCourt System: A Novel Study of 100 Professional Footballers at FIFA Medical Centre of Excellence Dubai UAE - Ghrairi M; Dalal S; Esteban-García E; Chomier P; Valle X; Pruna R (Dove Medical Press, 2023)
Mourad Ghrairi,1,2 Shaival Dalal,3 Esther Esteban-García,4 Philippe Chomier,5 Xavier Valle,2 Ricard Pruna2 1Department of Sports Medicine, FIFA Medical Centre of Excellence, Dubai, United Arab Emirates; 2Department of Sports Medicine, FIFA Medical Centre of Excellence FC Barcelona, Barcelona, Spain; 3Department of Orthopedics and Sports Medicine, Arthro One Sports Injuries and Rehabilitation Centre, Ahmedabad, Gujarat, India; 4Department of Physiotherapy, FIFA Medical Centre of Excellence, Dubai, United Arab Emirates; 5Department of Rehabilitation, FIFA Medical Centre of Excellence, Dubai, United Arab EmiratesCorrespondence: Shaival Dalal, Arthro One Orthopaedic Centre, 4th Floor, NIRAMYA, Near Rajpath Club, Bodakdev, Ahmedabad, 380054, India, Tel +91-9904915211, Email shaival_dalal@yahoo.co.inPurpose: The SpeedCourt system has been confirmed as an effective and dependable tool for evaluating multi-directional change-of-direction (COD) maneuvers. It has also been employed in the rehabilitation process following Anterior Cruciate Ligament (ACL) injuries and for multi-directional training purposes. This study investigated by means of the SpeedCourt system determines 1) whether there is any difference in COD parameters and countermovement jumps (CMJ) between United Arab Emirates (UAE) and non-UAE professional footballers 2) whether there is any difference between the two lower limbs during change-of-direction manoeuvres.Methodology: This analysis included 100 professional football players from UAE or Non-UAE football clubs who were tested at FIFA Medical Centre of Excellence. With the help of Speedcourt system, 6-s tapping, countermovement jump (CMJ) and chase 15-s tests were performed. Comparison was done between UAE and non-UAE footballers and also between the dominant and non-dominant sides.Results: Out of the 100 players, 83 players were right foot dominant. Apart from the countermovement jump test, there was no significant difference in results between UAE and non-UAE football players. Average time to turn for dominant and non-dominant sides did not show any significant difference, for either group.Conclusion: There is no difference in 6-s tapping, Chase 15-s tests or limb asymmetry amongst UAE and Non-UAE footballers. However, the non-UAE footballers showed significantly better performance in Countermovement Jump Test. The data provide baseline values for forthcoming sports medicine research, which can be taken into account when creating injury prevention or return-to-sport protocols, particularly with regard to change of direction parameters and countermovement jump.Keywords: Speedcourt, rehabilitation, prevention, countermovement